Perspective of Monitoring Heavy Metals by Moss Visible Chlorophyll Fluorescence Parameters - Chen, Yang-Er; Wu, Nan; Zhang, Zhong-Wei; Yuan, Ming; Yuan, Shu (Frontiers in Plant Science, 2019)
Chlorophyll fluorescence measurements have been mainly applied to investigate the functioning of the photosynthetic apparatus in the diagnosis of environmental stress. Moss is sensitive to several abiotic stresses and is considered an environmental indicator. Therefore, moss chlorophyll fluorescence can be as a visual parameter applicable for monitoring heavy metal contaminants in water. Different from previous studies with value changes of chlorophyll fluorescence in mosses, we suggest that phenotypes with anthocyanin accumulation pattern and chlorosis pattern and colors of chlorophyll fluorescence images of the maximum efficiency of PSII photochemistry (Fv/Fm) and the quantum yield of PSII electron transport (ΦPSII) could reflect metal species groups and concentrations roughly. And we further indicated that Cr(III) and Cr(VI) could be monitored distinguishably according to the non-photochemical quenching (NPQ) fluorescence of sporadic purple and sporadic lavender images respectively. It is interesting that the fluorescence color patterns were nearly the same for all treatment concentrations. This perspective provides additional data of chlorophyll fluorescence changes in moss under cold, heat, salinity, high light or osmotic stress. Only heat stress and high light have significant effects on the fluorescence parameters of Fv/Fm and ΦPSII. In contrast, mosses are less sensitive to short-term cold, salinity and osmotic stress. While NPQ decreases rapidly under the osmotic stress. Nevertheless, heat stress, high light or osmotic stress does not usually co-occur in the place where the moss grows. Estimation through moss chlorophyll fluorescence color patterns is still a rapid and non-invasive method to monitor heavy metal pollutions in water.